Intellectual property at the firm-level in the UK: the Oxford firm-level intellectual property database - Helmers, C; Rogers, M; Schautschick, P (University of Oxford, 2011)
This paper provides an overview of a new database that contains intellectual property data - in the form of patents and trademarks - for the population of firms registered in the UK. The paper discusses the principal challenges involved in the construction of this integrated database and provides an explanation of the approach taken to address these issues. We employ the integrated dataset to provide descriptive evidence on the firm-level use of intellectual property - including patents and trademarks - in the UK over the period 2000-2007.